Developing communication and thinking skills in English as a Foreign Language Education undergraduate students: a proposal for a syllabus model - Delgado-Crespo, Violeta; Gil, Vicky; Mur-Dueñas, Pilar; Pellicer-Ortín , Silvia (Onomázein, 2020)
It is our aim to share a proposal for a new syllabus model and learner-centered methodology for English as a Foreign Language students in the Degree in Teaching in Primary Education at the Universidad de Zaragoza (Spain), presenting the theoretical tenets and analyzing samples of resources and materials that have been designed. In a context of great diversity of levels and learning profiles in the abovementioned educational setting, it is no longer valid to conceive this part of teacher training only in terms of language proficiency, but rather it is necessary to equip students with learning to learn tools and metacognitive strategies as well as materials and resources purposefully designed bearing in mind their context, professional interests and linguistic needs. As a result, throughout the three 6 ECTS courses in the Degree (English in Primary Education I, II and III, for 1st, 2nd and 4th year students respectively) we seek to implement active methodologies and make use of a variety of resources following Communicative Language Teaching and Task-based Instruction principles, such as the following: (i) Deep Learning (Clark, 2009a, 2009b) and Scaffolded, Visible Thinking (Ritchhart, Church, and Morrison, 2011); (ii) Cooperative Learning (Kagan and Kagan, 1994); (iii) ICTs and EdTech; (iv) reflective learning, promoting self-assessment and peer-assessment, and (v) Project Based Learning (BIE, 2003). Overall, the teaching proposal designed has enabled us to partially respond to heterogeneity in our large classes and make our students’ learning of a language relevant and meaningful.